Cendekia Bitara Award - Nabilah Filzah, Mohd Radzuan (Faculty of Computing, 2021)
PEKAN 30 August 2021 - Congratulations to Associate Professor Ts. Dr. Mazlina Abdul Majid for being the recipient of Cendekia Bitara award for Journal Publication category.